Scalar Field Dynamics beyond the Cosmological Standard Model - Shah, Neil. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Physics.; Advisor: Mark Hertzberg.; Committee: Nishant Agarwal, Lawrence Ford, Danilo Marchesini, Krzysztof Sliwa, and Alexander Vilenkin.; Keyword: Physics.